Schools of «agrarian taste» in the towns established by the National Institute for Colonization in the area of La Violada-Canal de Monegros I, Aragón - José María Alagón Laste; Mónica Vázquez Astorga (Espacio, Tiempo y Educación, 2015)
The present text analyzes the ‘Primary Schools of Agricultural Orientation’ (Escuelas primarias de orientación agrícola in Spanish), projected between the decades of 1940’s and 1960’s in the towns established by the INC (National Institute of Colonization) within the irrigated area of La Violada Monegros I: Ontinar del Salz (Zaragoza), El Temple (Huesca), Puilato (Zaragoza), Artasona del Llano (Huesca), San Jorge (Huesca) y Valsalada (Huesca). In fact the school of Ontinar was one of the firsts to be built within the delegation of the Ebro river and it established a baseline for those built later. It is interesting to analyze, from the documentation and the visit of the buildings themselves, the architectural typology used in this territory and the educational system of these schools work as a whole refection of the agrarian ideology of Francoism. This study takes into account the regulations of the education system at the time and the school models developed by other administrations such as the Ministry of National Education. This way it is possible to get a global analysis and establish similarities with other typologies of constructions by the INC in Spain.